Preservation of zebrafish genetic resources through testis cryopreservation and spermatogonia transplantation - Zoran Marinović; Qian Li; Jelena Lujić; Yoshiko Iwasaki; Zsolt Csenki; Béla Urbányi; Goro Yoshizaki; Ákos Horváth (Scientific Reports, 2019)
Abstract Zebrafish is one of the most commonly used model organisms in biomedical, developmental and genetic research. The production of several thousands of transgenic lines is leading to difficulties in maintaining valuable genetic resources as cryopreservation protocols for eggs and embryos are not yet developed. In this study, we utilized testis cryopreservation (through both slow-rate freezing and vitrification) and spermatogonia transplantation as effective methods for long-term storage and line reconstitution in zebrafish. During freezing, utilization of 1.3 M of dimethyl sulfoxide (Me2SO) displayed the highest spermatogonia viability (~60%), while sugar and protein supplementation had no effects. Needle-immersed vitrification also yielded high spermatogonia viability rates (~50%). Both optimal slow-rate freezing and vitrification protocols proved to be reproducible in six tested zebrafish lines after displaying viability rates of >50% in all lines. Both fresh and cryopreserved spermatogonia retained their ability to colonize the recipient gonads after intraperitoneal transplantation of vasa::egfp and actb:yfp spermatogonia into wild-type AB recipient larvae. Colonization rate was significantly higher in dnd-morpholino sterilized recipients than in non-sterilized recipients. Lastly, wild-type recipients produced donor-derived sperm and donor-derived offspring through natural spawning. The method demonstrated in this study can be used for long-term storage of valuable zebrafish genetic resources and for reconstitution of whole zebrafish lines which will greatly improve the current preservation practices.